LOX-1 Regulates P. gingivalis-Induced Monocyte Migration and Adhesion to Human Umbilical Vein Endothelial Cells - Li, Qian; Liu, Jianru; Liu, Wenyi; Chu, Yi; Zhong, Jinsheng; Xie, Ying; Lou, Xinzhe; Ouyang, Xiangying (Frontiers in Cell and Developmental Biology, 2020)
Porphyromonas gingivalis (P. gingivalis) is one of the main periodontal bacteria. This pathogen was reported to enhance monocyte migration and adhesion to endothelial cells in atherosclerosis. The scavenger receptor lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) plays a pivotal role in atherogenesis. The aim of this study was to investigate whether LOX-1 modulates P. gingivalis-mediated monocyte migration and adhesion to endothelial cells and how it works. The results showed that the migration and adhesion of monocytic THP-1 cells to human umbilical vein endothelial cells (HUVECs) were significantly enhanced when HUVECs or THP-1 cells were challenged with P. gingivalis. Meanwhile, the expression level of LOX-1 in both HUVECs and THP-1 cells were also significantly increased by P. gingivalis stimulation. It is well known that ligand/receptor pairs monocyte chemoattractant protein-1 (MCP-1)/CC chemokine receptor 2 (CCR2), selectins/Integrins, and cell adhesion molecules (CAMs)/Integrins mediate monocyte migration and adhesion to endothelial cells. In this study, LOX-1 was demonstrated to be crucially involved in P. gingivalis-induced THP-1 cell migration and adhesion to HUVECs, by regulating expression of ligands MCP-1, intercellular adhesion molecule-1 (ICAM-1) and E-selectin in HUVECs and that of their receptors CCR2 and Integrin αMβ2 in THP-1 cells. The nuclear factor-kappa B (NF-κB) signaling pathway was proved to be involved in this process. In conclusion, LOX-1 plays a crucial role in P. gingivalis-induced monocyte migration and adhesion to endothelial cells. This result implies LOX-1 may act as a bridge in linking periodontitis to atherosclerosis.